2014
DOI: 10.1186/1476-9255-11-21
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CXCL-8 expression in bronchoalveolar lavage correlates with disease severity in patients with acute respiratory distress syndrome resulting from tuberculosis

Abstract: BackgroundTuberculosis (TB) is a rare but known cause of acute respiratory distress syndrome (ARDS). The role of inflammatory cytokines in the progression of ARDS in TB patients is unknown.ObjectivesIn this study we investigated the possible link between the levels of inflammatory cytokines in bronchoalveolar lavage (BAL) in patients with TB or ARDS alone or in patients with TB-induced ARDS (ARDS + TB).Methods90 patients were studied: 30 with TB alone, 30 with ARDS alone and 30 with ARDS + TB. BAL was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Taken together, the global gene expression analyses show significant up regulation of inflammation, cellular immunity and tissue damage networks in the lung granulomas of active TB patients. These observations are consistent with previous reports showing elevated expression of CXCR-4, CCL-3, CXCL-8, MMP-1 and -9 (matrix metalloproteinases) in the sputum, blood, lymph node, bronchoalveolar lavage (BAL) fluid and lungs of chronic, progressive pulmonary TB patients [ 19 , 26 31 ]. Importantly, mRNA for the most highly expressed inflammatory proteins included MMPs, CCL3 and CXCL8, which have previously been shown to be capable of driving the maturation/cavitation of lung TB granulomas and disease progression [ 17 , 28 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
“…Taken together, the global gene expression analyses show significant up regulation of inflammation, cellular immunity and tissue damage networks in the lung granulomas of active TB patients. These observations are consistent with previous reports showing elevated expression of CXCR-4, CCL-3, CXCL-8, MMP-1 and -9 (matrix metalloproteinases) in the sputum, blood, lymph node, bronchoalveolar lavage (BAL) fluid and lungs of chronic, progressive pulmonary TB patients [ 19 , 26 31 ]. Importantly, mRNA for the most highly expressed inflammatory proteins included MMPs, CCL3 and CXCL8, which have previously been shown to be capable of driving the maturation/cavitation of lung TB granulomas and disease progression [ 17 , 28 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
“…Pro-inflammatory cytokines, IL-8 and IL-12, involved with neutrophilic response, appeared in higher levels among patients with LTD. IL-8 induces NET release in human neutrophils (59) and has been associated with autoinflammatory profile in inflammatory bowel diseases and COPD (74, 75), with autoimmune diseases mediated by neutrophils (76) and with tuberculosis pathogenesis (77, 78). We also evaluated the role of galectin-3 and metalloproteinases (MMP-1 and 8) in the LTD as they may be associated with neutrophil activation (79).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that CXCL5 participates in the development of lung cancer [18,19]. In addition to their function in tumor progression, the CXC-chemokines were reported to be related to the development of ARDS, including CXCL8 [20], CXCL10 [21], and CXCL1 [22]. CXCL5 and the previously studied CXC-chemokines (CXCL8, CXCL10, and CXCL1) all belong to the same family.…”
Section: Discussionmentioning
confidence: 99%